Bosnia and Herzegovina’s Renewable Energy Policy and Perspective - Tokic, Amir; Akinci, Tahir Cetin; Zengin, Aydin Tarik (International Journal of Energy Economics and Policy, 2020)
Bosnia and Herzegovina is one of the richest countries in the Balkans in terms of renewable energy sources. Although Bosnia and Herzegovina has energy sources such as geothermal, solar and wind, the primary sources of electricity supply are from hydroelectric power plants and thermal power plants. The share of these two sources in total consumption is 62%. Drina attracts investors in the sector with nearly 200 hydroelectric power generation projects located on big and other small rivers such as Neretva, Bosnia, Una, Trebisnjica and Vrbas. According to Bosnia and Herzegovina 2019 data, it has an electricity generation capacity of approximately 18,000 GW. It is ranked ninth in the world in terms of hydroelectric power. Also, renewable energy potential in Bosnia and Herzegovina, such as wind, biomass and geothermal energy, is quite high. Especially the southern part of the country has been identified as the corridor of wind energy. In the examinations made, it has been determined that Bosnia and Herzegovina’s performance coefficient in wind energy potential is above 30% of the EU average. However, the country’s population density includes sensitive situations for new energy investments due to migration and geopolitical reasons. Despite this, the successful progress in the European Union negotiations and the laws enacted in the field of renewable energy also offer very attractive investment areas. In this study, a prospective approach was made regarding the renewable energy policy of Bosnia and Herzegovina, the economic approach of the country to renewable energy and the renewable energy policies of the government were discussed. Keywords: Bosnia and Herzegovina, Renewable Energy, Renewable Energy Policy, Energy Perspective. JEL Classifications: Q2, O2, N74, F13. DOI: https://doi.org/10.32479/ijeep.9777